Citizens in the Lab: Performance and Validation of eDNA Results. (16th December 2021) - Tøttrup, Anders P.; Svenningsen, Lea; Rytter, Maria; Lillemark, Marie Rathcke; Møller, Peter; Knudsen, Steen Wilhelm
Citizen Science has traditionally been applied in biodiversity monitoring, as the approach holds the potential for conducting large-scale data collections. However, involving citizens in more than data collection is still in its infancy. In this paper, we present the results of an ongoing citizen science project that expands the partnership between citizens and researchers by involving citizens in several parts of the scientific process. In the project, citizens first conduct sampling in the field, followed by analysis of their samples in our university laboratory. Finally, participants are interpreting the results of the laboratory analyses in collaboration with the researcher. The project aims to evaluate the presence of marine animals by monitoring the DNA left behind by the organisms in the environment (eDNA), using samples from the years 2017 and 2018. We found that citizens can carry out eDNA surveillance with an average success rate of 72% (where the success rate is defined as passing both the negative and positive control test) and that their data is of similar quality as a trained researcher and concur with known species distributions. Engaging and training citizen scientists in advanced laboratory analysis, such as the monitoring of eDNA in water samples, has promising applications for large-scale national monitoring of marine species that can be used in governmental mapping and monitoring efforts.